Adaptability and stability of maize hybrids in unreplicated multienvironment trials - Santos, Diego; Pereira, Carlos; Nunes, José Airton; Lepre, André (Revista Ciência Agronômica, 2018)
In maize breeding programs conducted by private companies, it is common to perform the product advanced trials (PAT) in several cultivation environments in order to better recommend the new hybrids, as well as to provide opportunities for the farmers to evaluate their products. The aim of this study was to describe the adaptability and stability of maize hybrids from unreplicated PATs using a multivariate approach combined with univariate methods. We considered the grain yield data of twelve maize hybrids evaluated in a PATs network conducted by the company DuPont Pioneer in 80 cultivation environments in the states of Minas Gerais and Goias, in second-crop of 2014. The AMMI analysis was employed and additionally we applied the methods based on bisegmented linear regression, Lin and Binns index (1988) and Annicchiarico index (1992). Significant differences were verified among the tested hybrids. The macro-environmental variation and the effect of hybrid by environment (H x E) interaction were expressive. The application of the AMMI method allowed the study of the H x E interaction based on maize PATs. Hybrids 7 and 8 are recommended for higher quality environments, while hybrids 3, 5 and 12 present wide adaptability. The Lin and Binns (1988) and Annicchiarico (1992) indexes highlight the hybrid 8 as the most promising for associating high productivity and lower risk in the tested cultivation environments.